2011
DOI: 10.1007/s00296-010-1763-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between dermatomyositis and papillary thyroid cancer: a case report

Abstract: Hashimoto's thyroiditis (HT) is found in a high proportion of resected thyroid specimens. There has been considerable controversy as to whether having HT predisposes a patient to papillary thyroid cancer (PTC) and conflicting data have been reported with regard to Hashimoto thyroiditis (HT) and risk of malignancy. The aim of this study was to evaluate coexistence of papillary thyroid cancer (PTC) with HT. Materials and methods: This is a retrospective study done at American Hospital 2 from April 2011 until Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Moreover, Antonelli et al reported a high prevalence of PTC (3.2%) in patients with SLE [ 4 ]. Also, a number of case reports show the association of DM and PTC [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Antonelli et al reported a high prevalence of PTC (3.2%) in patients with SLE [ 4 ]. Also, a number of case reports show the association of DM and PTC [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Atrophoderma 1 27 Polymyositis 1 28 Dermatomyositis 8 [29][30][31][32][33] Perforating collagenosis 1 34 Myelopathy 1 35 Ectopic hCG secretion 2 24, this case Ectopic parathyroid hormone secretion 1 36 Panuveitis 1 37 Syndrome of inappropriate antidiuresis 1 38 Cerebellar syndrome and sensory ganglionopathy 1 39 Epidermolysis Bullosa Acquisita 1 40 Propriospinal myoclonus 1 41 Systemic lupus erythematosus 1 42 Polymyalgia rheumatica 1 43 Retinopathy 1 44 Neutrophilia & eosinophilia due to granulocyte-macrophage colony-stimulating factor 1 45 FTC Leukocytosis 1 46 Hypertrophic osteoarthropathy 1 47 ATC Ectopic hCG secretion 5 5 Hypertrophic osteoarthropathy 1 48…”
mentioning
confidence: 99%
“…There are reports supporting the association between autoimmune diseases, especially RA, SLE, and DM, and an elevated risk of malignancy 9 11 . Meanwhile, limited cases suggest the association between MCTD and malignancies 5 .…”
Section: Discussionmentioning
confidence: 99%